Pelatihan dan Pendampingan Strategi Digital Marketing UMKM di Desa Situ Pondoksalam Purwakarta - Arsyad, Dea (STIE Syariah Indonesia Purwakarta, 2023)
The lack of understanding and practice of digital marketing for some Micro, Small and Medium Enterprises (MSMEs) in Situ Village, Pondoksalam District, Purwakarta Regency is an interesting phenomenon to study. It is important for MSME actors to be given an understanding of marketing by utilizing technology. This Digital Marketing Strategy Training Program is implemented so that people can market their MSME products effectively and efficiently, so as to achieve sales that meet the target. The purpose of this Community Service (PKM) is to provide training and assistance to the people of Situ Village, Pondoksalam Subdistrict, so that the community can explore their potential and actualize it by utilizing digital technology in terms of marketing MSME products. The method used in this PKM uses an education and training approach. The conclusion of this PKM MSME actors understand more about the importance of product marketing by utilizing digital technology, and how to use the marketplace in marketing the products produced by MSME actors. Then the PKM support program, the community feels helped by the existence of an accounting application socialization program that can make it easier for the people of Situ Pondoksalam village to manage finances. In addition, the socialization of halal certification for MSMEs was welcomed positively by the people of Situ Village, because products that have halal certification are able to convince buyers that their products have been properly verified. The benefits felt by the children were being able to get more insight into school lessons from the teaching that had been given by the PKM team.